Pelaksanaan Investigasi Ombudsman RI Perwakilan Sumatera Barat Pada Masa Pandemi Covid-19 demi Mewujudkan Pelayanan Publik Bebas Maladministrasi di Kota Padang - Fajri Tio Alhidayah; Adil Mubarak (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine the implementation of the investigation by the Indonesian Ombudsman Representative for West Sumatra during the Covid-19 Pandemic, to determine the Inhibiting Factors in the Implementation of the Investigation by the Indonesian Ombudsman Representative from West Sumatra during the Covid-19 Pandemic and to find out what efforts were carried out by the Indonesian Ombudsman Representative for West Sumatra in The Covid-19 Pandemic Period to Realize Maladministration-Free Public Services in the City of Padang. This type of research is a semi-qualitative research. The results of this study, namely: 1. The investigation of the Ombudsman RI Representative of West Sumatra has been running as regulated by Article 7 of Law no. 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. 2. When carrying out an investigation in Padang City, the Ombudsman encountered obstacles such as limited human resources for the Indonesian Ombudsman Representative for West Sumatra, the lack of budget for the RI Ombudsman for the West Sumatra Representative, poor communication between the Ombudsman and the community, and poor communication with the reported agencies resulting in a lack of supervision over warnings. Ombudsman. 3. The efforts of the Indonesian Ombudsman Representative for West Sumatra during the Covid-19 Pandemic to realize maladministration-free public services in the city of Padang, namely the efforts of the Indonesian Ombudsman Representative of West Sumatra to build a network and the efforts of the Indonesian Ombudsman Representative of West Sumatra in carrying out socialization.